Ethiopia: Constitutional Protection of Ethnic Minorities at the Regional Level - Van der Beken, Christophe (Afrika Focus, 2007)
It is argued that in order to evaluate the capacity of the Ethiopian federal structure to accommodate ethnic diversity and to regulate ethnic conflicts, the research cannot be limited to an analysis of the constitutional mechanisms at the federal level. One of the crucial features of the Ethiopian federal structure is that it provides its nine regions with the power to enact their internal constitutions. This implies that each and every region has the power to develop its own internal state structure, within a minimum federal framework. From here it follows that the federal structure to have the potential to lay the foundations for a viable Ethiopian state, it is essential that not only the federal but also the regional constitutional mechanisms have the capacity to realize unity in diversity. As is explained in this article, not a single Ethiopian region is ethnically homogeneous. The ethnic diversity which characterizes the federal level is therefore also present at the regional level. Therefore, when evaluating the capacity of the Ethiopian state structure to accomplish unity in diversity one also has to include an analysis of the regional mechanisms. The latter analysis is the core objective of this article. Key Words: Federal Constitution, Regional Constitutions, Ethnic Diversity